Production of Polyvinyl Alcohol Oxidase by a Symbiotic Mixed Culture - Shimao, Masayuki (1982)
Production of polyvinly alcohol (PVA) oxidase by Pseudomonas sp. strain VM15C, a PVA degrader of a symbiotic PVA-utilizing mixed culture, was examined in various cultures. Despite the absence of PVA in the culture in nutrient broth, VM15C showed approximately the same productivity of PVA oxidase activity as that in the culture with PVA as the sole carbon source, whereas the productivity in the culture with glucose was lower than that of either the nutrient broth or the PVA culture. PVA oxidase activity produced in the nutrient broth culture was predominantly present in the cells, and most of the activity appeared to be in the cytoplasm. In contrast, in the culture with PVA as the sole carbon source, the activity was present in the culture fluid in a larger ratio than in the nutrient broth culture. Thus, production of PVA oxidase activity by this strain was constitutive and repressible, although localization of the produced activity was changed by growth conditions.